2021
DOI: 10.1111/jnc.15374
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus‐1/simian immunodeficiency virus infection induces opening of pannexin‐1 channels resulting in neuronal synaptic compromise: A novel therapeutic opportunity to prevent NeuroHIV

Abstract: Despite the successful introduction of antiretroviral therapy (ART), at least half of the human immunodeficiency virus-1 (HIV)-positive population develop some degree of HIV-associated neurocognitive disorder, but the mechanisms are still under active investigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 114 publications
(198 reference statements)
0
21
0
Order By: Relevance
“…ATP released through these open Panx1 channels in the extracellular environment binds to purinergic P2 receptors, which drive the activation of NLRP3 inflammasomes [ 44 , 45 , 46 , 47 ]. Furthermore, Panx1-mediated ATP release has been associated with viral infections, replication, and pathogeneses [ 20 , 21 , 48 , 49 ]. It was previously shown that anti-inflammatory drugs [ 50 , 51 ] and antiviral drugs [ 52 ] are able to alter Panx1 channel activity.…”
Section: Resultsmentioning
confidence: 99%
“…ATP released through these open Panx1 channels in the extracellular environment binds to purinergic P2 receptors, which drive the activation of NLRP3 inflammasomes [ 44 , 45 , 46 , 47 ]. Furthermore, Panx1-mediated ATP release has been associated with viral infections, replication, and pathogeneses [ 20 , 21 , 48 , 49 ]. It was previously shown that anti-inflammatory drugs [ 50 , 51 ] and antiviral drugs [ 52 ] are able to alter Panx1 channel activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, only ATP was predictive of the early stages of cognitive decline in the HIV-infected population [ 110 ]. We identified that viral reservoirs, myeloid and astrocytic, can release ATP, contributing to the purinergic dysfunction [ 33 , 111 , 112 ]. We also identified that residual expression of gp120 and virus could activate Panx-1 and Connexin-43 hemichannels in several cell types, further increasing ATP release during chronic HIV infection.…”
Section: Crusade To Find Reliable Biomarkers To Identify Chronic and ...mentioning
confidence: 99%
“…Our data in simian immunodeficiency virus (SIV)-infected macaques indicate that blocking Panx-1 channel opening after SIV infection prevents immune compromise, leukocyte differentiation induced by the virus, transmigration into the CNS, and loss of complex synapses [ 33 , 110 ]. These data indicate that despite the complex animal model, mimetic peptides to Panx-1 can be used to prevent CNS damage and improve immune response.…”
Section: Panx-1 and Purinergic Signaling Axis In Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropilin-1 (NRP-1) and Cluster of Differentiation 147 (CD147) can interact with furin cleaved SARS-CoV-2 spike protein since furin preactivation of the S protein increases the binding affinity to its receptor and cofactors, resulting in a widespread infectious cycle introducing differences in comparison to SARS-CoV despite both viruses targeting ACE2 (84). With reference to other RNA viruses, HIV-1 infection was found to induce the opening of ubiquitously expressed Pannexin-1 (Panx-1) channels on the surface of peripheral blood mononuclear cells, leading to a release of ATP that could stimulate purinergic signaling pathways that enhanced viral binding, accelerating HIV infectious entry and contributed to the compromised synaptic function found in cases of HIV-associated neurocognitive disorder (85). It was proposed SARS-CoV-2 may also induce opening of the large ionic Panx-1 channels, allowing passive outflux of ATP, metabolites and other small anions likely to have a role in exacerbating the inflammatory response (86).…”
Section: Sars-cov-2 Interactions With the Purinomementioning
confidence: 99%